Effects of temperature shocks on economic growth and welfare in Asia - Minsoo Lee; Mai Lin Villaruel; Raymond Gaspar (Asian Development Bank (ADB), 2016)
Using the Burke, Hsiang, and Miguel (2015) framework, we examine the nonlinear response effect of economic growth to historic temperature and precipitation fluctuations. We confirm that aside from the significant effect of rising temperature on agricultural production, industrial production and investment endeavors also serve as other potential channels through which temperature significantly affects overall economic productivity. We find the overall economic productivity of developing Asia to be at least 10% lower by 2100 relative to business as usual. We also empirically analyze policy measures and factors that could help countries mitigate consumption volatility driven by climate change-related events. Consistent with several microlevel findings, financial inclusiveness helps households mitigate consumption volatility amid temperature change. Likewise, government plays a critical role in moderating the negative impact of rising temperature in both output and consumption.
Keywords: I30; Q54; Q58; 330; climate change; consumption volatility; developing Asia; global warming